Photoelectric emission from gas solids - Davletov, Askar; Dmitriev, Yu.A. (Recent Contributions to Physics, 2015)
Electron photoemission from rare gas solids (RGS) is obtained using VUV open discharge sources. Temperature dependencies of the photoyield are measured by recording the ECR absorption of free electrons emitted from the RGS surfaces.
Keywords: photoemission, solid gas, free electrons